Análisis de la huella ecológica personal de la estratificación de la población del campus La Matriz de la Universidad Técnica de Cotopaxi. - Jerez Venegas, Carmen Cecilia (2023)
The Ecological Footprint is an environmental indicator, which allows revealing the global hectares that a person or population needs to meet the daily needs in consumption of natural resources and assimilation of waste generated in daily activities. The study of this environmental indicator allows us to recognize the rate of affectation that is caused to the natural environment and opt for a sustainable lifestyle, and in this way externalize a less negative impact on the planet's resources.